Media Ombudsman: Opportunities and Challenge to Media Self-regulation - วงรุจิระ ผู้ช่วยศาสตราจารย์ ดร.มนวิภา (Journal of Digital Communications, 2017)
The purposes of this study intended to examine 1) the opportunity and challenge of mass media self-regulation through media ombudsman 2) international experiences of media ombudsman and 3) the factors which might support or hinder their workห. The study applied document analysis and in-depth interview. News editors and executive editors of both newspapers and broadcasting media were the key informants in this study. Theoretical frameworks were based on media self-regulation and media ombudsman concepts. The findings showed that 1) both Thai newspapers and broadcasting media had set up media ombudsman committee in their organization. While the Press Council was the key organization initiating this system of self-regulation among its members, broadcasting media on the other hand were required by NBTC regulation to establish this organ. 2) In the U.S. media ombudsmen usually were former senior editors and working alone, whereas in Japan they worked in the form of committees. In both countries, the ombudsman not merely received complaint from readers/audiences but monitored the coverage and contents of its media. 3) The factors affecting the work of self-regulation by media ombudsman included: the policy of media organization executives, internal communication among its staff, especially editorial staff, freedom of media ombudsman and their understanding of media professionalism, as well as clear guidelines, rules and directions of self-regulation under media ombudsman. The main goal will be self-regulation to enhance media credibility and accountability.